2023
DOI: 10.1111/vox.13544
|View full text |Cite
|
Sign up to set email alerts
|

Safety and protection of plasma donors: A scoping review and evidence gap map

Natalie Schroyens,
Tine D'aes,
Emmy De Buck
et al.

Abstract: Background and ObjectivesAs part of a large‐scale project to safely increase plasma collection in Europe, the current scoping review identifies the existing evidence (gaps) on adverse events (AEs) and other health effects in plasmapheresis donors, as well as factors that may be associated with such events/effects.Materials and MethodsWe searched six databases and three registries. Study characteristics (publication type, language, study design, population, outcomes, associated factors, time of assessment, dura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…For the initial scoping review [5], 17810 records were identified from databases and registers. After removal of duplicates, 7209 records were screened, resulting in the inclusion of 97 papers and registrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the initial scoping review [5], 17810 records were identified from databases and registers. After removal of duplicates, 7209 records were screened, resulting in the inclusion of 97 papers and registrations.…”
Section: Resultsmentioning
confidence: 99%
“…We did not include studies that compared the health of first-time or new donors to that of repeat donors [42,43] or investigated health effects in donors with different cumulative numbers of plasma donations [44,45]. We did, however, identify these studies systematically in the framework of our scoping review [5]. Several retrospective studies found no effect of the number of donations made in the previous 12 months on iron levels, protein levels, immunity markers, red cell and iron metabolism, cardiovascular risk, or risk of (osteoporotic) fractures [41,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid selective outcome reporting, evidence on donor-reported or staff-reported adverse events, and objectively measured physiological parameters, hematological parameters, iron metabolism parameters, coagulation factors, and protein levels should also be considered when formulating overall conclusions. 10 For example, evidence from a RCT (submitted for publication), 11 and two cohort studies 12,13 showed that very-high frequency plasma donation (up to two times per week) may result in significant and clinically relevant reductions in IgG levels. Moreover, 12.4% of donors in the first SIPLA study, which was conducted in Germany, were deferred because of low levels of IgG investigating the impact of intensive plasmapheresis with up to 60 donations per year.…”
Section: Methodological Shortcomingsmentioning
confidence: 99%
“…We agree that self‐perceived health (via the SF‐36 4 ) is important but it is only one indicator/dimension of donor health. To avoid selective outcome reporting, evidence on donor‐reported or staff‐reported adverse events, and objectively measured physiological parameters, hematological parameters, iron metabolism parameters, coagulation factors, and protein levels should also be considered when formulating overall conclusions 10 . For example, evidence from a RCT (submitted for publication), 11 and two cohort studies 12,13 showed that very‐high frequency plasma donation (up to two times per week) may result in significant and clinically relevant reductions in IgG levels.…”
Section: Methodological Shortcomingsmentioning
confidence: 99%